Relationship Between Menarche Age and Body Mass Index (IMT) Youth in Palembang City - Linardi, Felicia; Aditiawati; Minerva Riani Kadir (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Concern regarding secular trend of declining age of menarche has increased in the last few decades. Prevalence of childhood and adolescents obesity in Indonesia has also increased lately while some studies suggest that increased body mass index associates with the early onset of puberty which known to be the risk factor of many health problems. This study aims to investigate whether age of menarche is associated with body mass index in adolescents in Palembang. Sample of this cross sectional designed study was elementary and junior high school girls from 8 schools in Palembang taken with stratified random sampling. A total of 388 respondents met the inclusion criteria. Age of menarche and body mass index got from the questionnaire and anthropometric examination were analysed using Chi-square test. Out of 388 respondents, 49,5% experienced menarche at the earlier age than the mean age of menarche of 12,36 years and 20,1% were classified as overweight and obese. The average menarcheal age of overweight and obese respondents was earlier than those classified as normal and underweight. This study proved that there is a highly significant association between age of menarche and body mass index with the p-value of 0,000 (Chi-square test). There is a highly significant association between body mass index during peripubertal period and the age of menarche. Strict monitoring on body mass index of elementary and junior high school girls is necessary to prevent early puberty.